Surgeon Leadership Style and Risk-Adjusted Patient Outcomes - Shubeck, Sarah P. (Surg Endosc, 2018)
BACKGROUND: There are many reasons to believe that surgeon personality traits and related leadership behaviors influence patient outcomes. For example, participation in continuing education, effective self-reflection, and openness to feedback are associated with certain personalities and may also lead to improvement in outcomes. In this context, we sought to determine if an individual surgeon’s thinking and behavior traits correlate with patient level outcomes after bariatric surgery. METHODS: Practicing surgeons from the Michigan Bariatric Surgery Collaborative (MBSC) were administered the Life Styles Inventory (LSI) assessment. The results of this assessment were then collapsed into 3 major styles that corresponded with particular patterns of an individual’s thinking and behavior: Constructive (achievement, self-actualizing, humanistic-encouraging, affiliative), Passive/Defensive (approval, conventional, dependent, avoidance), and Aggressive/Defensive (perfectionistic, competitive, power, oppositional). We compared patients level outcomes for surgeons in the lowest, middle, and highest quintiles for each style. We then used patient level risk adjusted rates of complications after bariatric surgery to quantify the impact surgeon style on post-operative outcomes. RESULTS: We found that patients undergoing bariatric surgery performed by surgeons with high levels of Constructive (achievement, self-actualizing, humanistic-encouraging, affiliative) and Passive/Defensive (approval, conventional, dependent, avoidance) styles had lower rates of adverse events compared with surgeons with low levels of the respective styles (High Constructive: 14.7% [13.8%-15.6%], Low Constructive: 17.7% [16.8%-18.6%]; High Passive: 14.8% [13.4%-16.1%], Low Passive: 18.7% [17.3%-19.9%]). Conversely, surgeons identified with high aggressive styles (perfectionistic, competitive, power, oppositional) had similar rates of postoperative adverse events compared with surgeons with low levels (High Aggressive: 15.2% [14.3%-16.1%], Low Aggressive: 14.9% [14.2%-15.6%]). CONCLUSION: Our analysis demonstrates that surgeons’ leadership styles are correlated with surgical outcomes for individual patients. This finding underscores the need for professional development for surgeons to cultivate strengths in the constructive domains including intentional self-improvement, development of interpersonal skills, and the receptiveness to feedback.